The Slower, the Better: Wide Complex Tachycardia Triggered by Flecainide in an Elderly Female - Ebubechukwu Ezeh; Maddie Perdoncin; Morgan K. Moroi; Mohammad Amro; Mohammed Ruzieh; Paul I. Okhumale (Case Reports in Cardiology)
Class IC antiarrhythmics are generally considered a safe means of treating many common arrhythmias such as atrial fibrillation (a-fib), atrial flutter (a-flutter), and paroxysmal supraventricular tachycardia (PSVT). Essentially, flecainide works by binding and blocking sodium channels more effectively at higher heart rates. However, this class of drugs is known to exhibit use dependence which could predispose patients to the development of malignant arrhythmias during episodes of tachycardia. In this case, we present a patient who was being treated with flecainide for a-fib who ultimately developed a wide complex tachycardia after her metoprolol was held.